Dietary diversity and development among early childhood children in rural China - Qin, Yanyan; Yue, Ai; Zhang, Yali; Zhang, Xinyue; Gao, Yuan; Liang, Shibin; Song, Qiannan; Qiao, Na (Frontiers in Public Health, 2024)
BackgroundEarly childhood is a critical period for cognitive development, heavily influenced by nutrition. Despite significant economic advancements, malnutrition and micronutrient deficiencies persist in many low- and middle-income countries, including China, where dietary diversity remains suboptimal. Existing research predominantly relies on correlational data, underscoring the need for more rigorous empirical evidence. This study aims to fill that gap by providing stronger empirical evidence on the relationship between dietary diversity and developmental outcomes in rural Chinese children.MethodsWe conducted a longitudinal cohort study of 1,207 children aged 6–23 months, drawn from 100 villages across 22 counties in rural China, with three follow-up rounds extending until the children reached 51–83 months of age. Cognitive and non-cognitive development, as well as key health indicators, were evaluated. Cognitive development was measured using the Bayley Scales of Infant and Toddler Development and the Wechsler Preschool and Primary Scale of Intelligence Fourth Edition. Non-cognitive development was assessed via the Ages and Stages Questionnaire: Social-Emotional and the Strengths and Difficulties Questionnaire. Health indicators included anemia, frequency of illness in the past 2 weeks, and four key anthropometric measures (height-for-age z-scores, weight-for-age z-scores, weight-for-height z-scores, and body mass index-for-age z-scores). Multiple linear regression models were applied to analyze the relationship between dietary diversity scores (DDS) and developmental outcomes, incorporating child fixed effects and adjustments for time-variant confounders. We accounted for the hierarchical structure of the data by clustering standard errors at the village level, which also reflects the township level.ResultsThe regression analysis identified significant positive associations between DDS and cognitive (p < 0.01), as well as reduced illness incidence (p < 0.001) in children aged 6–54 months. Additionally, DDS demonstrated a strong positive effect on non-cognitive development (p < 0.001) in children 2 years and older. The associations between DDS, non-cognitive development (p < 0.01), and illnesses reduction (p < 0.001) remained robust under two-way fixed effects models.ImplicationsTo promote sustainable improvements in child development and health, policymakers should prioritize nutrition-focused interventions in rural areas. Community-based programs offering caregivers training and nutritional support, integrated within healthcare and social services infrastructures, are vital for ensuring families have the necessary resources enhance child wellbeing and long-term developmental outcomes.